Respuesta :

The simplified version of (5x^4y^-3)^-2 would be y^6/25x^8 (this is a fraction)

Hope this helps :)

For this case we must simplify the following expression:

[tex](5x ^ 4 * y ^ {-3}) ^ {-2}[/tex]

By definition of power properties we have:

[tex]a ^ {-1} = \frac {1} {a ^ 1}[/tex]

So:

[tex](5x ^ 4 * y ^ {-3}) ^ {- 2} =\\(5x ^ 4 * \frac {1} {y ^ 3}) ^ {- 2} =\\\frac {1} {(\frac {5x ^ 4} {y ^ 3}) ^ 2} =\\\frac {y ^ 6} {25x ^ 8}[/tex]

Answer:

[tex]\frac {y ^ 6} {25x ^ 8}[/tex]

ACCESS MORE